Design and fabrication of an electrochemical sensor for the measurement of adherent cells' viability (2017)
Single-cell measurements have appeared in the need to obtain real time viability information with a high resolution. The following thesis aims to design and fabricate a lab-on-a-chip device that allows the detection of adherent cells viability via electrical impedance sprectroscopy (EIS). The device is tested with Vero cells at different culture times and compared with traditional MTT viability assay. Two equivalent circuits have been found to describe the behavior of the device with and without the cell culture. The studied device gives and insight of the possibilities of electrochemical measurements in single-cell experiments